Hubungan Pengetahuan Dan Sikap Keluarga Dengan Pelaksanaan PHBS Rumah Tangga Di Pekon Tanjung Rejo Kecamatan Bangkunat Kabupaten Pesisir Barat - Umi Romayati Keswara; Wahid Tri Wahyudi; Andriyanto Andriyanto (Universitas Malahayati Lampung, 2020)
ABSTRACT: RELATIONSHIP OF FAMILY KNOWLEDGE AND ATTITUDE WITH IMPLEMENTATION OF HOUSEHOLD PHBS IN PEKON TANJUNG REJO KECAMATAN BANGKUNAT KABUPATEN WEST COUNTRY Background : PHBS is still needed and practiced in daily life, because the impact of behavior on health status is quite large, so various efforts are needed to change unhealthy behavior to be healthy. Pekon Tanjung Rejo is located in Bangukunat Subdistrict, the achievement of PHBS from 2013-2016 has fluctuated, where in 2013 with the achievement of PHBS of 66.9%, in 2014 the achievement of PHBS was 73.8%, in 2015 of 38.07% and in 2016 it decreased again to 32.19%. Purpose : it is known the relationship between knowledge and attitudes of families with the implementation of PHBS in Pekon Tanjung Rejo Sub-District Bangkunat District West Coast District in 2019.Methods : Quantitative research type, cross sectional design. The study population was all household heads in the puskesmas area. Sampling was purposive sampling based on the criteria desired by the researcher. The variables studied were family knowledge, family attitudes, and PHBS household arrangements. data collection using questionnaires distributed to respondents. The study was conducted in March - April 2019. Data analysis was univariate and bivariate (Chi Square).Result : based on the results of the study most of the behavior is not household PHBS as many as 113 (64.9%) respondents. Most knowledgeable about household PHBS is not as good as 95 (54.6%) respondents. Most of them have negative PHBS Household attitudes as many as 93 (53.4%) respondents. There is a relationship between knowledge with household PHBS behavior (p-value 0,000; OR: 4,046). There is a relationship between attitude and PHBS behavior in the household (p-value 0,000; OR: 5,316). Suggestions Pekon Tanjung Rejo Bangkunat Subdistrict in collaboration with cross-sectors to do re-triggering per RW / RT in the community environment that still does not behave PHBS and provide practical stimulants related to PHBS. Conclusions : There is a relationship between knowledge and attitudes with PHBS behavior of households in Pekon Tanjung Rejo Bangkunat Subdistrict, West Coast Regency in 2019. Suggestions are expected to be more intensive and actively involved in collaboration to hold regular counseling on the importance and benefits of PHBS. Keywords: knowledge, attitude, PHBS INTISARI: HUBUNGAN PENGETAHUAN DAN SIKAP KELUARGA DENGAN PELAKSANAAN PHBS RUMAH TANGGA DI PEKON TANJUNG REJO KECAMATAN BANGKUNAT KABUPATEN PESISIR BARAT Latar Belakang: PHBS masih diperlukan dan dipraktekkan dalam kehidupan sehari-hari, karena dampak dari perilaku terhadap derajat kesehatan cukup besar, maka diperlukan berbagai upaya untuk mengubah perilaku yang tidak sehat menjadi sehat. Pekon Tanjung Rejo terletak di Kecamatan Bangukunat, pencapaian PHBS dari tahun 2013-2016 mengalami fluktuatif, dimana tahun 2013 dengan pencapaian PHBS sebesar 66,9%, di tahun 2014 dengan pencapaian PHBS sebesar 73,8%, ditahun 2015 sebesar 38,07% dan ditahun 2016 mengalami penurunan kembali menjadi sebesar 32,19%.Tujuan penelitian: diketahui hubungan pengetahuan dan sikap keluarga dengan pelaksanaan PHBS Rumah Tangga di Pekon Tanjung Rejo Kecamatan Bangkunat Kabupaten Pesisir Barat tahun 2019.Metode Penelitian : Jenis penelitian kuantitatif, rancangan cross sectional. Populasi penelitian seluruh kepala rumah tangga yang ada di wilayah puskesmas, sampel berjumlah 174 orang, pengambilan sampel secara purposive sampling. pengambilan data menggunakan kuesioner yang dibagikan ke responden. Penelitian telah dilakukan bulan Maret – April 2019. Analisis data secara univariat dan bivariat (Chi Square).Hasil Penelitian : sebagian besar berperilaku tidak PHBS Rumah Tangga yaitu sebanyak 113 (64,9%) responden. berpengetahuan PHBS Rumah Tangga kurang baik yaitu sebanyak 95 (54,6%) responden. sikap PHBS Rumah Tangga negatif yaitu sebanyak 93 (53,4%) responden. Ada hubungan pengetahuan (p-value 0,000; OR: 4,046) dan sikap (p-value 0,000; OR: 5,316) dengan perilaku PHBS Rumah Tangga.Kesimpulan : Ada hubungan pengetahuan dan sikap dengan perilaku PHBS Rumah Tangga di Pekon Tanjung Rejo Kecamatan Bangkunat Kabupaten Pesisir Barat tahun 2019. Saran diharapkan lebih intensif dan terlibat aktif dalam kerjasama mengadakan penyuluhan berkala tentang pentingnya dan manfaat dari PHBS. Kata kunci : pengetahuan, sikap, PHBS